Hubungan Kausal Gaya Evaluasi Kinerja Anggaran, Kepuasan Kerja dan Kinerja pada Perguruan Tinggi di Yogyakarta dengan Pendekatan Structural Equation Modeling - Sriyono Sriyono; Ari Pratono (BISMA (Bisnis dan Manajemen), 2018)
Performance measurement is essential for any organization. Performance is a measure of success in achieving organizational objectives. The results of performance measurement as a reference for management to do the planning organization. The budget is the target organization's performance to be achieved in one period to come. Evaluation of budget execution is performed to determine the occurrence of budget deviations, by comparing the budget with the realization. Budgetary performance evaluation style have an important role in assessing the implementation of the budget. Budgetary performance evaluation style is considered appropriate to evaluate the performance of subordinates, because the subordinate approval of budgetary performance evaluation style is seen as an important element of the relationship between budgetary performance evaluation style with the performance of subordinates as reflected in the attitudes and behavior of subordinates that shows job satisfaction. This study aims to examine the relationship style of performance evaluation of the budget based on budget constrained style (BCS) on performance by measuring the job satisfaction of employees within the College of Yogyakarta.Analysis tools used for testing the hypothesis is Structural Equation Modelling (SEM). The analysis showed that: The style of performance evaluation of the budget (GEKA) were statistically significant positive effect on job satisfaction (KK). Job Satisfaction (KK) were statistically significant positive effect on performance (K). While the budgetary performance evaluation style (GEKA) statistically have no effect on performance (K)